Performance and egg quality of Embrapa 051 laying hens subjected to different feeding programs - Silva, Suelen Nunes da; Forgiarini, Juliana; Alves, Débora Aline; Krabbe, Everton Luis; Avila, Valdir Silveira; Lopes, Débora Cristina Nichelle; Xavier, Eduardo Gonçalves (Medicina Veterinária, 2020)
This study aimed to evaluate the productive performance and egg quality of Embrapa 051 lineage laying hens compared to a commercial line (Lohmann Brown) when subjected to different feeding programs. Trial consisted of a randomized complete block design, with four treatments: T1 - Lohmann Brown Line receiving 100% basal diet; T2 - Embrapa 051 Line receiving 93% basal diet; T3 - Embrapa 051 line receiving 100% basal diet; and T4 - Embrapa 051 lineage receiving 107% basal diet. The treatments had five replicates each. The basal diet was that recommended by the Lohmann Brown line manual. Variables of bird performance (egg weight, egg production rate, feed conversion per dozen eggs, energy conversion and egg mass) were analyzed, as well as internal egg quality (Haugh unit, yolk color, yolk percentage, and albumen percentage) and external egg quality (specific gravity, shell percentage, and shell thickness). All performance variables presented significant differences (P <0.05) in the three evaluated cycles, comparing lineages. Egg produced by the Embrapa 051 line had the highest percentages of yolk and those of the Lohmann Brown line had the highest percentage of albumen. In conclusion, Embrapa 051 lineage has the potential to produce good quality eggs, as long as it receives the same feeding program of the genetically established lineage.